Conductometric Studies on Temperature Dependence and Thermodynamics of Ion-Association of Leucinatobis(biguanide) Cobalt(III) Complexes - Sanahal Singh, L.; David Singh, Th.; Yaiphaba, N.; Rajmuhon Singh, N. (Asian Journal of Chemistry, 2010)
The conductivity measurements over a wide range of temperatures between 5 to 50 ºC were made in dilute aqueous solutions of the chloride and bromide of leucinatobis(biguanide) cobalt(III) complexes. The ionassociation constants (KA) obtained by using the method of Jenkins and Monk had minimum values at temperatures (tmin), characteristics of the anions. The remarkable increases of the KA values with decreasing temperatures below (tmin), were ascribed due to specific short range interactions between the amino-acid ligands of the complexes and halide atoms of the anions in the contact ion pairs. The thermodynamics properties viz. changes in entropy, enthalpy and free energy which enable to study the nature of the ion-association had also been calculated using the values of KA. Using Stoke's law and Bjerrum relationship, the sizes of the ionpairs had also been calculated.